Measures to protect and promote elite athletes` mental health in Swiss sports. Current status and areas for improvement - Röthlin, P.; Horvath, S.; Birrer, D. (Sports Psychiatry, 2023)
Abstract:Introduction: This paper addresses the growing concern surrounding mental health in elite sports. Acknowledging that national sports systems vary in structure and that any evaluation of these issues must necessarily be country-specific, the study explores current mental health provisions in Switzerland. Method: Based on the feedback of 31 experts, including athletes and representatives from sporting organizations, the study evaluates four aspects of existing measures: formulation of a mental health plan, mental health care provision, athlete support systems, and provisions for high-risk events. Results: The findings highlight two key issues. First, experts clearly have different views about mental health initiatives in Swiss sports for reasons that may include variations in access to information, program visibility, regional and sport-specific differences, and emerging strategies that have not yet been widely embraced. Second, despite these disparities, the experts unanimously agreed that some basic mental health measures remain unimplemented. Conclusion: These findings highlight a pressing need for basic interventions such as mental health screening and improved mental health literacy. Another recommended priority is to design and implement a holistic national mental health plan informed by the collaborative contributions of all stakeholders. Furthermore, this discourse on mental health must be in coordination with ongoing dialogues on ethics in sports.